Rethinking Islamic Anatolian Space - Hurol, Yonca; Numan, İbrahim (Cambridge Scholars Publishing, 2008)
There are some misunderstandings regarding the spatial characteristics of historical, Islamic, Anatolian architecture. The history of architecture highlights its abstractness and order, however, it also ignores its strong relationship with nature and the environment. On the other hand, it is known that the unity of all beings is the essence of Islamic, Anatolian culture. Unity indicates a tendency towards order and abstractness as well as multiplicity. The research objective of this paper is to question the abstractness of Islamic, Anatolian space with the help of the analysis of two Turkish novels.
The aim of this book title is to understand the meaning of the Islamic architecture from a contemporary point of view.
Keywords: Islamic architecture, space, mediations